Characterizing rhizospheric plant growth promoting bacteria for their effects on oat (Avena Sativa) (Funded work) - SANDEEP KUMAR GUPTA,; JAY KISHOR PRASAD,; RICHA RAGHUWANSHI, (International Journal of Pharma and Bio Sciences, 2017)
Plant growth promoting rhizobacteria (PGPR) are group of useful microorganism that colonize plant rhizosphere and enhance growth by their various direct and indirect effects on plants. In our present study, 30 bacterial strains were isolated from rhizospheric soil of wheat, rice and black gram crop. Plant growth promoting traits selected for screening bacterial isolates were IAA production, p-solubilization, ammonia production, HCN production and extra cellular enzyme production like catalase and amylase. In addition, growth of PGPR isolates was optimized under different temperature and pH. Out of the 30 isolates, 4 isolates viz SG-13, SG-14, SG-16 and SG-18 were found to be promising for the plant growth promoting attributes studied. The isolates were then tested on Avena sativa (Haritika RO-19) under pot conditions for their effects on seed germination and vigour index and were found to promote growth and seed germination. They also increased water stress tolerance in oat plants by enhancing root proliferation and improving relative water content (RWC) in leaf and significantly increasing root shoot ratio as compared to uninoculated control. These bacterial isolates can be potential biofertilizers in crop management under water stress field conditions.